2000
DOI: 10.1212/wnl.55.10.1591
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial analysis in autosomal dominant hereditary spastic paraplegia

Abstract: of memory deficits and behavioral changes characterized by lack of drive, loss of interest, and depression over the previous 6 months. Since the age of 36 years, she had five episodes of severe and sustained physical activity, with a sense of euphoria and intermittent irritability, followed by a period of remission or episodes of unreasonable guilt about her past acts, anxiety, and reported slowing of thought. Neuropsychological evaluation evidenced a severe overall mental decline (MMSE score 8/30). She appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…We did not find functional, biochemical or morphological OXPHOS defects in two patients harbouring SPG4 mutations, in agreement with the putative nuclear localization of spastin and with previous data [23]. This is different from experimental data in the SPG7-related form.…”
Section: Discussionsupporting
confidence: 78%
“…We did not find functional, biochemical or morphological OXPHOS defects in two patients harbouring SPG4 mutations, in agreement with the putative nuclear localization of spastin and with previous data [23]. This is different from experimental data in the SPG7-related form.…”
Section: Discussionsupporting
confidence: 78%
“…Letters refer to sequence at nucleotide 159 of the NIPA1 cDNA sequence. Clinical features (Fink et al 1995a), muscle biopsy (Hedera et al 2000 ), and genetic features (Fink et al 1995b) of ADHSP-ARK1 have been reported elsewhere. The ADHSP-IRQ1 kindred was ascertained through the University of Michigan Neurology Outpatient Clinic.…”
Section: Figurementioning
confidence: 78%
“…Below age ten, ATL1- related HSP (SPG3A) is a frequent cause of HSP. Regarding prognosis, the progression rate in this subgroup of HSP is generally slow, and wheelchair dependency or need for a walking aid (cane, walker, or wheelchair) is relatively rare [ 20 ]. In our current study, there were four children with a mutation in the ATL1 gene, of whom one was described earlier [ 13 ].…”
Section: Discussionmentioning
confidence: 99%